Currency demand approach and underground economy in Qatar - Jauhari B Dahalan; Awadh Ahmed Mohammed Al-Gamal (Proceedings of AICS - Social Sciences, 2017)
The growth of the underground economy has become a serious challenge and concern to the official economy of many countries. Based on the adjusted currency demand function this paper estimates the magnitude of the underground economy behind tax evasion in Qatar over the period of 1980-2010. The results show that the average of the underground economy in Qatar constitutes 17.03% of the official GDP. While, the average of the tax evasion as a percent of the total non-oil tax revenues estimated at 16.50% and at 2.12% of the official GDP respectively.